In vivo footprinting studies suggest a role for chromatin in transcription of the human 7SK gene. - Boyd, D; Greger, I; Murphy, S (2000)
Mutation and deletion analyses of mammalian class III small nuclear RNA genes transcribed by RNA polymerase (pol) III have defined three functional promoter elements: a distal sequence element (DSE) at around -220, a proximal sequence element (PSE) at around -60 and a TATA box at around -30. Although binding studies have identified factors that bind to these sites in vitro, it is not known exactly how proteins interact with the promoters of these genes in vivo. In this study, we have used dimethyl sulphate and DNase I treatment of HeLa cells and nuclei, respectively, followed by linker-mediated polymerase chain reaction, to obtain in vivo footprints of proteins binding to the promoter of the Pol III-transcribed 7SK gene. Our results show that most of the characterised promoter elements of this gene are protected in vivo in these cells, and the pattern of DNase I protection suggests that a nucleosome lies between the DSE and the PSE. Methylation protection was also seen upstream of the DSE over a sequence corresponding to the binding site of a POZ domain-containing protein, ZID, which interacts with components of histone deacetylase complexes. These findings suggest that chromatin structure plays a role in the cascade of protein-DNA interactions that regulate expression of this pol III-transcribed gene.